A Drowning Sunda Shelf Model during Last Glacial Maximum (LGM) and Holocene: A Review - Solihuddin, Tubagus (Indonesian Journal on Geoscience, 2014)
DOI:Â 10.17014/ijog.v1i2.182Rising sea levels since the Last Glacial Maximum (LGM), some ~20,000 years ago, has drowned the Sunda Shelf and generated the complex coastal morphology as seen today. The pattern of drowning of the shelf will be utilized to assess likely timing of shoreline displacements and the duration of shelf exposure during the postglacial sea level rise. From existing sea level records around Sunda Shelf region, âsea level curveâ was assembled to reconstruct the shelf drowning events. A five stage drowning model is proposed, including 1) maximum exposure of the shelf at approximately 20,500 years Before Present (y.B.P.), when sea level had fallen to about -118 m below present sea level (bpl.), 2) melt water pulse (MWP) 1A at ~14,000 y.B.P. when sea level rose to about -80 m bpl., 3) melt water pulse (MWP) 1B at ~11,500 y.B.P., when sea level was predicted around -50 m bpl., 4) Early-Holocene at ~9,700 y.B.P, when sea level was predicted at about-30 m bpl, and 5) sea level high stand at ~4,000 y.B.P., when sea level jumped to approx. +5 m above present sea level (apl.). This study shows that the sea level fluctuated by more than 120 m at various times during LGM and Holocene. Also confirmed that sea level curve of Sunda Shelf seems to fit well when combined with sea level curve from Barbados, although the comparison remains controversial until now due to the considerable distinction of tectonic and hydro-isostatic settings. Â